اثر الثقافية التنظيمية على الاداء الوظيفي - - غزالي عبد الفتاح (جامعة البليدة2؛ كلية الحقوق والعلوم السياسية, 2024)
عالجت الدارسةةةةةةةةةةةةةل قافةةةةةةةةةةةةةاى الأد الالاظل البمديريل عوز ا ااك الاءيوا غرد د ل ا ال د اك ال ا م، البا هةدظةت عط يد د اارسةةةةةةةةةةةةةةل قطةداةيةل لو ة عط ي يعةل ة لأطد 2022-2016لوجازئد العةامةةةةةةةةةةةةةةرةل الرب طد ا ل عوز الاةاةا ا ط يدتةت ظط ةا االةةةةةةةةةةةةةة ةاليةل البةاليةل قةا ها الأد الالةاظةل البمديريةل عوز ا ااك ؟ إلز 2022 2016الاءيوا غرد د ل ا ال د اك ال ا لوجازئد العامةةةةرل الل الوبدم الرربدم طط جاةب ال عط قعدظل ي يعل الالاظل البمديريل ظا الرؤسسل ق ل الدراسل إذا قا كان ؤلأد غياب ق ان ات د قط ق اةات هذه الالاظل عوز الب لأطد العام ل ا عوز ا ااك الاءيوا، إفةةةةةةةةةةةةةةاظل إلز قسةةةةةةةةةةةةةةاهرل الالاظل البمديريةةل ظا إتةةدات الب ططد اايجةةا ا اااةةل الرةةد د ةةل قةةدا ظعةةالطب ةةا ظا البةة لأطد عوز ا ااك العةةام ل ةةذه الرد د ل، دج إابيار ى الالاظل البمديريل كان اراسةل قافةا ان هذا ا اط د م قط اهم الراافةي الر رل ظا قجال إاارم الراارا ال شةةةةةةةد ل لرا ل ا قط قسةةةةةةةاهرل غال ل ظا الب لأطد عوز ا ااك الاءيوا عوز ا ااك العام لورمدرل ك ل. قةةاقةةت الةةدارسةةةةةةةةةةةةةةةل عوز قجراعةةل قخبووةةل قط الرمةةاهو ااقبادغةةا ت قسةةةةةةةةةةةةةةبمةةدم ظا ذلةة عوز الرلتدةةل 351 ااسةةةةب يان ك اا ا غ عوز عطمل قدرت ةةةةةةةةةةةةةةةةةة ق الأا عوز قسةةةةباا قد د ل ا ال د اك ال ا لوجازئد العامةرل، امةوت المبائو إلز ان الرؤسةسةل ق ل الدارسةل برب الاظل مديريل عد لل بال إلز وعطل إعاام ا ا ظا الراارا ال شةةةةةةةةةد ل عويا إقبدتت الدارسةةةةةةةةةل ظ د طط ا ل ا قد لل بلا ل عد ل الالاظل البمديريل ظد قخدجات الدارسةةةةةةةةةةةات اااار ل ال د ال ظا هذا الشةةةةةةةةةةة ن الااةيل برال ظا العرل ظد اةدرل قعواقا يل تد ال ق ب دم قط ق ل ال ات لضران سطد الرعواقل القيم البمديريل غش ل قماسب. الكلمات المفتاحية: الالاظل البمديريل، ا ااك الاءيوا، قد د ل ا ال د اك ال ا لوجازئد العامرل. Abstract : The study addressed the topic of the impact of organizational culture on job performance at the Directorate of Electricity and Gas Distribution in Algiers from 2016 to 2022. Through a field study, it aimed to explore the nature of the influence of the first variable on the second, posing the following research question: What is the impact of organizational culture on job performance at the Directorate of Electricity and Gas Distribution in Algiers during the period 2016–2022? Additionally, the study sought to understand the nature of the organizational culture within the institution under investigation and whether the absence of one component of this culture affects its overall impact on job performance. The study also examined the contribution of organizational culture to fostering positive change within the directorate and its effectiveness in influencing overall performance. The choice to study organizational culture was based on its significant importance in the field of human resource management, given its substantial contribution to job performance and the overall performance of the organization as a whole. The study relied on a variety of methodologies and approaches, using observation and a questionnaire as research tools, applied to a sample of 351 respondents from the Directorate of Electricity and Gas Distribution in Algiers. The findings revealed that the organization under study possesses a wellestablished organizational culture that requires activation and reinforcement within its human resources. Accordingly, the study proposed two main ideas: the first involves strengthening and adjusting the organizational culture in line with the outcomes of modern administrative studies in this field, while the second focuses on implementing innovative information systems designed by the researcher to ensure the proper flow of information and organizational values. Keywords : organizational culture, job performance, Directorate of Electricity and Gas Distribution in Algiers.
دراسة حالة مديرية توزيع الكهرباء والغاز للجزائر العاصمة 2016-2022م
Keywords: الثقابية التنظيمية; الكهرباء; الغاز